HUBUNGAN USIA DENGAN PENINGKATAN TEKANAN DARAH POST HEMODIALISA PADA LANSIA DI RUMAH SAKIT IHC LAVALETTE KOTA MALANG - Taufan Arif; Anggy Dwi Pramesty; Joko Wiyono; Sulastyawati Sulastyawati (Poltekkes Kemenkes Malang, 2024)
Abstract: While undergoing hemodialysis therapy, patients experience health problems, including hemodynamic disorders, which are a common problem. Factors that cause changes in post-hemodialysis blood pressure can be caused by age. Elderly patients undergoing hemodialysis treatment experience an increase in blood pressure after hemodialysis by 80%. A possible factor causing an increase in post-hemodialysis blood pressure is age. The aim of this study was to determine the relationship between age and increased post-hemodialysis blood pressure. The research design uses a